Islamic Archipelago Perspective in Symbolic Interpretation of Ngalaksa Customary Local Wisdom in Sumedang Regency, West Java - Ahmad Saebani, Beni; Sutiana, Yana (Faculty of Law, Universitas Pekalongan, 2024)
Each ethnic community has a leader who controls its social and cultural communication. The leadership is equipped with its own territory, social norms, and traditional arts. The arts as a product of this culture are integrated with the community's belief in something metaphysical and supernatural, which is deified and believed to be the creator and ruler of the universe universally. Such as the “Ngalaksa” custom carried out by the Rancakalong community in Sumedang Regency every year. This custom is a symbol of gratitude to God for all the blessings that have been bestowed in the form of agricultural products. This research will answer about the symbolic meaning contained in the Ngalaksa custom and its contribution to the embodiment of traditional culture of the people in the archipelago as well as a religious understanding of the divine values contained in the Sundanese Ngalaksa custom. This research uses descriptive analysis method and anthropological approach with qualitative data collected by observing, interviewing, and participating with the implementation of Ngalaksa custom in Rancakalong, Sumedang. This research reveals that the Ngalaksa custom in Rancakalong, Sumedang, has a deep meaning in the context of empowering thinking, acting, and creating based on the teachings of Islam Nusantara. The cultural symbols of this custom are interpreted through Islamic values that strengthen the character and spirituality of individuals and communities, strengthening faith in God with practices that reflect the harmony of religion and local culture.